2018
DOI: 10.1016/j.ssmph.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping geographic clusters of food security and health: Where do social determinants and health outcomes converge in the U.S?

Abstract: We identified overlapping geographic clusters of food insecurity and health across U.S. counties to identify potential shared mechanisms for geographic disparities in health and food insecurity. By analyzing health variables compiled as part of the 2014 Robert Wood Johnson Foundation County Health Rankings, we constructed four health indices and compared their spatial patterns to spatial patterns found in food insecurity data obtained from 2014 Feeding America's County Map the Meal Gap data. Clusters of low an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…For example, high deprivation areas had higher premature deaths and a higher percentage of people reporting fair or poor health, adult smokers, adults who are obese, and adults who are physically inactive when compared to the other deprivation groups. Leonard et al, found that poor health and high clusters of food insecurity were common in the Mississippi Delta, Black Belt, Appalachia, and Alaska (Leonard et al, 2018). Our findings are supported by this paper and illuminate how social determinants of health are key to understanding the spatial distribution between material deprivation and adverse health outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, high deprivation areas had higher premature deaths and a higher percentage of people reporting fair or poor health, adult smokers, adults who are obese, and adults who are physically inactive when compared to the other deprivation groups. Leonard et al, found that poor health and high clusters of food insecurity were common in the Mississippi Delta, Black Belt, Appalachia, and Alaska (Leonard et al, 2018). Our findings are supported by this paper and illuminate how social determinants of health are key to understanding the spatial distribution between material deprivation and adverse health outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…The maps developed in the study can provide policy makers, medical and lay health professionals alike, with insight into socioeconomic factors that are likely to influence adverse health outcomes for their patients (Kind & Buckingham, 2018). We recognize the barriers to changing the health status of disadvantaged communities, such as financial limitations of the tax base in high NDI areas with subsequent limited investment and available resources for healthy living (Leonard et al, 2018;Center FR & A). Our maps also demonstrate the clustering of limitedresource communities, which exacerbates these barriers.…”
Section: Future Directionsmentioning
confidence: 99%
“…A recent geographic analysis by Leonard and colleagues focused on identifying overlapping areas of food insecurity and determinants of health outcomes indicating overall poor health in the United States. Although there were limitations to this analysis, geographic clustering of food insecurity and concurrent poor health indicators tended to be present in Southeastern US regions with higher non‐Hispanic Black populations and higher poverty rates …”
Section: Introductionmentioning
confidence: 99%
“…One study found similar spatial clustering of poor physical and mental health and food insecurity in these areas (27). Counties in trajectory 8 that were not part of geographic clusters may have unique factors that explain their poor mortality rates and rate trajectories that warrant further exploration.…”
Section: Discussionmentioning
confidence: 90%